KINERJA PERTUMBUHAN BENIH IKAN NILA (Oreochromis niloticus) DALAM SISTEM KOLAM AIR TERGENANG DENGAN TINGKAT PEMBERIAN PAKAN BERBEDA - Ricky Djauhari; Shinta Sylvia Monalisa; Amaya Sena Wahyuni; Ivone Christiana; Irawadi Gunawan; Petrus Senas; Yanetri Asi Nion; Aris Toteles; Riamona Sadelman Tulis; Fatma Sarie; Lamria Simamora; Tatik Zulaika; Dewi Klarita Furtuna (Universitas Mataram, 2024)
The activity of cultivating nile tilapia in a stagnant water pond system allows fish to utilize resources in the form of natural food and commercial feed in a balanced manner, thereby reducing the amount of external feed. This research aims to evaluate the growth performance of tilapia fry in a stagnant water pond system with different feeding levels. This research was carried out using a completely randomized design (CRD) consisting of 3 treatments for rearing tilapia fry in a stagnant water pond system with different feeding levels with three replications each, namely 3% feeding rate, 4.5% feeding rate. % and feeding rate 6%. The test tilapia fish had an average initial weight of 2.66-3.06 g and were reared for 21 days with feed supplementation containing a commercial probiotic mix dose of 0.2% and a feeding frequency of 1 time per day. The results of the research showed that different levels of feeding had a significant effect (p<0.05) on feed efficiency, feed conversion ratio and amount of feed consumption, but could still provide optimum growth rates.